Analysis of the Causes and Effects of Noise from Rail Transport - Ficzere, Péter (International Journal of Engineering and Management Sciences, 2024)
Noise emissions from rail transport are a major concern, as they affect both the environment and people's health and quality of life. Among the many sources of noise emissions, rail vehicles and infrastructure are a major factor. With regard to rail noise emissions, it can be concluded that noise effects are influenced by a number of factors. These factors include train speed, track condition, traction technology and the noise abatement methods used. The negative effects of noise exposure include sleep disturbance, stress and mental health deterioration. It also affects the quality of life of people in urban areas and property prices. It should be emphasised that reducing noise emissions from rail transport is key to creating a healthier and more sustainable urban environment. To achieve this, it is important to use modern noise abatement technologies, improve infrastructure and implement noise abatement actions effectively. Transport authorities and railway companies should work together to achieve a more noise-free rail transport, to improve people's quality of life and to protect the environment.